PERSONAL SELLING DAN PERCEIVED VALUE MENJADI FAKTOR YANG MEMPENGARUHI PURCHASE DECISION TERHADAP GAS BUMI RUMAH TANGGA DI PERUSAHAAN SUBHOLDING GAS SURABAYA - Tasya Beby Bintara; Danis Maulana; Yesica Novrita Devi (Proceeding Maritime Business Management Conference, 2023)
Each company has its own strategy to promote and maintain its products in the market. The promotion that is considered the most effective and influential by the gas subholding company in this study is Personal Selling by forming a value perception towards customers. This study aims to determine the effect of personal selling and perceived value variables on purchase decisions. In this study, the sampling technique used was purposive sampling technique, namely 71 respondents. The method of completion in this study was using multiple linear regression analysis using the help of IBM SPSS version 26 software. The results of the analysis show that personal selling variables (????1) and perceived value (????2) have a positive and significant effect on purchase decisions. The conclusion of this study proves that with the implementation of good personal selling in a salesperson, it provides understanding to prospective customers about the products offered so that it will generate interest in the products offered. This is the same as having a high Perceived Value will change a good perception of prospective customers, where prospective customers who initially do not give their trust to household natural gas products become trusted and subscribe to become loyal customers so that personal selling and perceived value have an influence in increasing Purchase Decisions.